Feasibility study of hydrophilic and hydrophobic silica aerogels as drug delivery systems - Smirnova, Irina; Suttiruengwong, Supakij; Arlt, Wolfgang (Journal of Non-Crystalline Solids, 2004)
The feasibility of silica aerogels as oral drug delivery systems was investigated. Silica aerogels were loaded with several drugs by adsorption from their solutions in supercritical CO. It was demonstrated that for all three drugs investigated here, high loading of the aerogel could be achieved. The loaded aerogels were characterized by IR- and UV spectroscopy and X-ray diffraction in order to show that no degradation of the drugs occurred during the loading procedure. The release profiles of two drugs (ketoprofen and griseofulvin) from loaded aerogels were measured. It was found that the drugs adsorbed on hydrophilic silica aerogels dissolve faster than the corresponding crystalline drugs. This fact can be explained by both an increase in the specific surface area of the drug adsorbed on the aerogel and its non-crystallinity in this state. The influence of density and hydrophobicity of aerogels on both the adsorption and release of drugs were studied. ©2004 Elsevier B.V. All rights reserved.